Розвиток готельно-ресторанного бізнесу в умовах сьогодення - Баженова, С.; Пологовська, Ю.; Канцур, Інна Григорівна (Видавничий дім «Гельветика», 2022)
У статті розкрито практичні аспекти розвитку готельно-ресторанного бізнесу в Україні в сучасних умовах функціонування. Встановлено, що готельно-ресторанний бізнес як у період минулих років, так і зараз, перебуває у неочікуваних та несприятливих умовах. Визначено, що нестабільність економічної та політичної ситуації в Україні, пандемічні обмеження, військова агресія ворога негативно позначаються на динаміці розвитку та функціонування суб’єктів готельно-ресторанної індустрії. З метою забезпечення розвитку та ефективного функціонування суб’єктів готельно-ресторанної справи в умовах сьогодення в державі запроваджуються програми та проєкти підтримки цієї сфери економічної діяльності за сприянням міжнародних організацій

The article reveals the practical aspects of the development of hotel and restaurant business in Ukraine in modern conditions of operation. According to the results of the study, it is established that the hotel and restaurant business, both in the past years and now, is in unexpected and unfavorable conditions. In the field of hotel and restaurant business there are constant changes that correspond to certain modern trends and affect the level of competitiveness in the market. Today, the hotel and restaurant business is experiencing perhaps the most critical period in the history of independence. The global deployment of the COVID-19 pandemic, as well as the full-scale invasion of the enemy, has seriously affected this business, thus provoking its critical financial situation. The instability of the economic and political situation in Ukraine, pandemic restrictions, military aggression of the enemy have a negative impact on the dynamics of development and functioning of the hotel and restaurant industry. Analysis of statistical information shows that in 2020 compared to previous years there was a deterioration in the financial result (balance) before taxation of hotel and restaurant businesses, increased the share of unprofitable businesses in the hotel and restaurant business, decreased profitability and profitability of operating activities of hotels and similar temporary accommodation facilities and restaurants and mobile catering entities. At the beginning of 2022, the situation is even worse, because under the influence of military aggression by the enemy, the hotel and restaurant business has almost ceased to function effectively. However, in order to ensure the development and effective functioning of the hotel and restaurant business in the country, programs and projects are supported to support this area of economic activity with the assistance of international organizations.
Keywords: готельно-ресторанний бізнес; суб’єкт господарювання; пандемічні обмеження; воєнний стан; hotel and restaurant business; business entity; pandemic restrictions; martial law